PERANAN DEWAN PERWAKILAN DAERAH REPUBLIK INDONESIA DALAM PEMBAHASAN RANCANGAN UNDANG-UNDANG - , Y. Nanang Marjiyanto, SPd.,MPd, Joko Setiono S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Objective of the research was to obtain detailed description on Regional Representative Councilâs role in discussing legal draft, as a form of implementting Regional Representative Councilâs legislative function. The following was to identify limitation or restriction that Regional Representative Council faced to complete their role in discussing legal draft. Then, researcher also meant to know efforts to resolve those limitations. Research method used in the study was doctrinal or normative legal study combined with empirical study. Data taken was primary, secondary and tertiary legal material. To deepen and have cross-check data, it was done by interview with respondent who selected by purposive sampling, namely Chief of Regional Representative Council and General Secretary of Regional Representative Council. Data analysis used deductive method. Result of the research concluded that Regional Representative Councilâs role in discussing legal draft was just in First Level Discussion Stage, not until in decision one. Regional Representative Council was just as co-legislator of People Representative Council to discuss legal draft. The limitation of Regional Representative Councilâs role in discussing legal draft was including external and internal. External limitation was that legal regulation which becoming a legal fundamental itself restricted a implementation of Regional Representative Councilâs legislative function. The internal limitation was lied on organizational structure and additional tool of Regional Representative Council in conducting the duties optimally. Efforts done for resolving those problem was to propose amendment of Constitutional UUDâ45 or the change toward the legal executor in constitutional. The other effort was to collect expertâs ideas to strengthen fundamental of change idea.Keyword: legal draft discussion, legislative function, bicameralism